KEPUASAN PETANI TERHADAP PENYULUHAN PERTANIAN DI KELOMPOK TANI OTAUW MOKHO KAMPUNG SEREH DISTRIK SENTANI KABUPATEN JAYAPURA (Farmers' Satisfaction with Agricultural Extension in the Otauw Mokho Farmers Group, Kampung Sereh Sentani Distrik, Jayapura Regency) - NEKEN, APRISNOH JUNIUS SEVENHART; AHANG, YOHANES SANDRO; HARNI, ELISABET (Universitas Mulawarman (University of Mulawarman), 2026)
Agricultural extension is crucial for enhancing production and the well-being of farmers; however, how well it works relies on how satisfied farmers are with the services offered. This study seeks to evaluate the degree of farmer satisfaction with agricultural extension services in the Otauw Mokho Farmers Group, Sereh Village, Sentani District, Jayapura Regency. The research method used is descriptive quantitative with a saturated sampling technique applied to 20 members of the farmer group. Data were collected thru questionnaires, interviews, and observations, and then analyzed using scoring methods with a Likert scale. The research results show that the level of farmer satisfaction with agricultural extension services reaches 81.24% (very satisfied category), especially in the dimension of extension service quality. Meanwhile, satisfaction with extension support in marketing and farmer group development reaches 78.80% (satisfied category). Aspects that received high ratings include the communication skills of the extension workers, professional appearance, and the ability to provide new ideas for business development. However, the provision of production facilities and the use of social media for marketing still need to be improved. This research provides important input for formulating more effective extension strategies tailored to the needs of farmers in Jayapura Regency.